International Academic Exposure as a Means of Strengthening Students’ Global Mindset, Cultural Sensitivity, and Academic Motivation - Sukmawati S; Ifayani Haanurat; Sahabuddin Nanda; Wa Ode Rayyani; Asri Jaya; Zalkha Soraya; M. Yusuf. K; Muchriana Muchran (International Journal Of Community Service, 2026)
Strengthening students’ global competencies has become a critical challenge in the context of higher education in the era of globalization. Education is no longer focused solely on formal academic achievement, but also on the development of a global mindset, cultural sensitivity, and academic motivation as essential components of students’ readiness to engage in a multicultural global environment. One approach to addressing this challenge is through international academic exposure designed as part of community engagement activities. This article aims to describe the contribution of international academic exposure as a means of strengthening students’ global mindset, cultural sensitivity, and academic motivation within the context of higher education. The community service program was implemented using a descriptive–participatory approach with a hybrid model that combined offline international activities in Egypt and Saudi Arabia with online academic dissemination and reflection. A total of 12 lecturers from diverse educational backgrounds were involved as facilitators. Student participants consisted of 15 students who took part directly in offline international academic exposure activities and 438 students who participated online through reflective and dissemination activities. Data were collected through observation, discussions, structured reflections, and activity documentation, and were analyzed using a descriptive qualitative approach. The findings indicate that international academic exposure contributes to strengthening students’ global mindset, cultural sensitivity, and academic motivation, both intensively among offline participants and reflectively among online participants. These findings affirm that international academic exposure can serve as a relevant education-based community engagement model in supporting the internationalization of higher education.